Nível de maturidade em gerenciamento de projetos: levantamento nas indústrias do estado do Paraná - Kolotelo, Jorge Luciano Gil (2008)
The objective of this research was to evaluate the Project Management Maturity level at the Industries of Paraná State. The reorganization process, imposed by this new knowledge era, reinforces the need of new management models adjusted more effectively in order to accomplish the strategic objectives. The Project Management and consequently a greater maturity of its practices, has been a path adopted to achieve strategic goals and business throughout efficient projects. The inter-linkage and complexity of activities should be ensured by appropriate processes. To know the maturity level of these processes is to know if the company balances adequately the available resources and points out if there are readinesses of the firm for competition. The project management has been increasingly used by companies due its pervasive, multidisciplinary and because it requires a rethinking of the organizational structure demanding a wide range of competencies of managers and teams. This is a quantitative research using the survey method and it was initially developed as probabilistic and stratified sampling approach. From a population of about 31,000 companies listed in the Sistema FIEP, a set up was done for a universe about 1,900 to conduce 234 stratified sampling. The obtained return of 24 respondents triggered the review of the sampling approach to a mix of two non probabilistic sampling: dimensional (derived from the quota) and snowball sampling. The model MMGP-Prado was adopted, to measure the maturity in a 1 to 5 scale: initial, known, standardized, managed and optimized. The Project Maturity level found for the State of Paraná was 2,43. The results presented covers a variety of stratifications and, although it shall not be generalized, they are important for studies under maturity level and project management themes in companies of Paraná State. Yet, it is a snap shot in history, serves as a benchmark for improvement to the participating companies and the study is a characterization of starting point for measurements of this kind. Beyond that, the research delivered: the internet portal with the questionnaire; the questionnaire manual; the Project Management Maturity Panoramic view; and the level of maturity as baseline for future studies in assisting Project Management in the State of Paraná.